METODE K-MEANS CLUSTERING UUNTUK PEMETAAN GEDUNG OLAHRAGA RAGA BADMINTON DI SOLORAYA - Prasetyo, Danar Aji; Remawati, Dwi; Nugroho, Didik (STMIK Sinar Nusantara, 2023)
There are many Badminton Sports Buildings in the Soloraya area, including Sukoharjo Regency, Boyolali Regency, Klaten Regency, Wonogiri Regency, Karanganyar Regency, Sragen and Solo. Each Badminton Gymnasium has different conditions, starting from varying rental prices, as well as the various facilities offered by each Badminton Sports Hall. The purpose of this research is to help people in Soloraya find suitable badminton sports halls, an information system is needed that can explain the mapping of badminton sports halls in Soloraya. This study uses the K-Means and GIS methods to solve the problem of grouping badminton sports halls based on their categories. The result of this research is a geographic mapping information system to make it easier for people to find badminton courts that match the criteria of people in Soloraya.